2018
DOI: 10.11648/j.ajim.20180605.17
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Antimicrobial Resistance to <i>Escherichia Coli</i> Among the Urinary Tract Infection Patients in Bangladesh

Abstract: Urinary Tract Infection (UTI) is very common in our day-today clinical practice. Among all the organisms Escherichia coli (E coli) is the most common but antimicrobial resistance becomes an alarming issue for UTI management now a days. Aim of this study is to assess the pattern of antimicrobial resistance to E coli among the UTI patients in Jashore, Bangladesh. This observational study was conducted from February, 2017 to January, 2018 in the district of Jashore, Bangladesh. We recruited 696 patients of both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Urinary tract infection (UTI) is the second most common infection, affecting 150 million people, both males and females, annually worldwide 1‐5 . However, females are more susceptible to UTIs than males because their urethra is typically shorter and more conveniently located near the rectum, which makes them vulnerable to uropathogenic bacteria and causes infection 3,6‐12 .…”
Section: Introductionmentioning
confidence: 99%
“…Urinary tract infection (UTI) is the second most common infection, affecting 150 million people, both males and females, annually worldwide 1‐5 . However, females are more susceptible to UTIs than males because their urethra is typically shorter and more conveniently located near the rectum, which makes them vulnerable to uropathogenic bacteria and causes infection 3,6‐12 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that more than 75% of E . coli causing UTI are resistant to third-generation cephalosporin [ 16 ]. Existing reports are based on either a small sample size, targeting only a specific population or age group, analysis of retrospective data from hospital registry, or characterization of convenience samples of bacterial isolates obtained from urine samples of UTI patients [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out in 2012 among 443 suspected UTI patients in a regional medical college hospital in Bangladesh showed that 43% of patients had significant bacterial growth of uropathogens in their urine samples [15]. A recent study has shown that more than 75% of E. coli causing UTI are resistant to third-generation cephalosporin [16]. Existing reports are based on either a small sample size, targeting only a specific population or age group, analysis of retrospective data from hospital registry, or characterization of convenience samples of bacterial isolates obtained from urine samples of UTI patients [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…12 An alarming picture has been reflected by a recent study in Bangladesh, which demonstrated more than 75% of the E. coli causing UTIs are resistant to third-generation cephalosporins. 13 In Bangladesh UTI is a significant public health problem & increasing antibiotic resistance even complicates the treatment of uncomplicated UTI by increasing patient morbidity & health care costs due to frequent treatment failure, recurrent infections & unnecessary use of broad-spectrum antimicrobials. 10,14 There is no large-scale prospective survey of UTIs in Bangladesh, that can reflect the up-to-date burden of the infections & the antimicrobial susceptibility pattern in the community.…”
Section: Introductionmentioning
confidence: 99%